Homeodomain proteins in action: similar DNA binding preferences, highly variable connectivity. (April 2017) - Bobola, Nicoletta; Merabet, Samir
Abstract : Homeodomain proteins are evolutionary conserved proteins present in the entire eukaryote kingdom. They execute functions that are essential for life, both in developing and adult organisms. Most homeodomain proteins act as transcription factors and bind DNA to control the activity of other genes. In contrast to their similar DNA binding specificity, homeodomain proteins execute highly diverse and context-dependent functions. Several factors, including genome accessibility, DNA shape, combinatorial binding and the ability to interact with many transcriptional partners, diversify the activity of homeodomain proteins and culminate in the activation of highly dynamic, context-specific transcriptional programs. Clarifying how homeodomain transcription factors work is central to our understanding of development, disease and evolution.